(untitled) (International Journal of Business Innovation, 2023)
This article aims to analyze the scientific production on the impact of new technologies, such as blockchain, big data and artificial intelligence, on the professional day-to-day of accountants, quantifying the articles published by year, title of origin, citation, journal impact, as well as identifying publications by author, affiliation and country. 71 studies are analyzed using bibliometric techniques supported by the VOSviewer software. From the main conclusions, it appears that the journal with the most articles published on the subject is the Journal of Emerging Technologies in Accounting, with 11 published papers and the most influential author in the area and with one of the best h-index is Miklos Vasarhelyi.